The potential costs and distributional effect of Covid-19 related unemployment in Ireland - Keelan Beirne; Karina Doorley; Mark Regan; Barra Roantree; Dora Tuda (University of Essex, Institute for Social and Economic Research (ISER), 2020)
This paper simulates the impact that Covid-19 related job losses will have on family incomes and the public finances. It finds that in the central 'medium' unemployment scenario of 600,000 job losses, around 400,000 families will see their disposable income fall by more than 20 per cent in the absence of policy changes, with proportionately larger losses for those in higher income families. Measures announced by the Government - notably the flat-rate Pandemic Unemployment Payment of exteuro350 per week - reduce the numbers exposed to such extreme losses by about a third, but at significant cost to the Exchequer. The paper also finds that the additional cost of the Government's Temporary Wage Subsidy Scheme may be minimal, in part because its current design is less generous to lower earners than the Pandemic Unemployment Payment they would receive if laid off.
Keywords: D31; E24; H31; 330; covid-19; Ireland; tax-benefit policy; distribution